A Systematic Survey and Characterization of Enhancers that Regulate Sox3 in Neuro-Sensory Development in Comparison with Sox2 Enhancers - Hisato Kondoh; Tatsuya Takemoto; Yoshiko Ishida; Yoshifumi Kamimura; Naoko Nishimura; Masanori Uchikawa (Biology, 2012)
Development of neural and sensory primordia at the early stages of embryogenesis depends on the activity of two B1 Sox transcription factors, Sox2 and Sox3. The embryonic expression patterns of the Sox2 and Sox3 genes are similar, yet they show gene-unique features. We screened for enhancers of the 231-kb genomic region encompassing Sox3 of chicken, and identified 13 new enhancers that showed activity in different domains of the neuro-sensory primordia. Combined with the three Sox3-proximal enhancers determined previously, at least 16 enhancers were involved in Sox3 regulation. Starting from the NP1 enhancer, more enhancers with different specificities are activated in sequence, resulting in complex overlapping patterns of enhancer activities. NP1 was activated in the caudal lateral epiblast adjacent to the posterior growing end of neural plate, and by the combined action of Wnt and Fgf signaling, similar to the Sox2 N1 enhancer involved in neural/mesodermal dichotomous cell lineage segregation. The Sox3 D5 enhancer and Sox2 N3 enhancer were also activated similarly in the diencephalon, optic vesicle and lens placode, suggesting analogies in their regulation. In general, however, the specificities of the enhancers were not identical between Sox3 and Sox2, including the cases of the NP1 and D5 enhancers.